Flow field around a 5:1 rectangular cylinder using LES: Influence of inflow turbulence conditions, spanwise domain size and their interaction. (13th June 2017) - Ricci, M.; Patruno, L.; de Miranda, S.; Ubertini, F.
Highlights: The flow field around a 5:1 rectangular cylinder is studied in a turbulent flow by means of LES. The modifications occurring in the flow organization with varying characteristics of the incoming turbulence are reproduced. Covariance Proper Transformation is performed in order to characterize the flow modifications induced by incoming turbulence. Results are compared to experimental data in terms of pressure statistics distributions showing good results. Abstract: The flow field around the rectangular cylinder with aspect ratio 5:1 has been widely investigated in recent literature as a prototype of reattached flow around elongated bluff bodies like bridge decks and high rise buildings. Due to the technical importance of such flows, many research works have been proposed aiming at studying the accuracy of available simulation techniques in reproducing the flow organization. When Large Eddy Simulations (LES) are considered, to the authors' knowledge, the proposed contributions focused on perfectly smooth inlet conditions which, indeed, represent more an exception than a rule in Computational Wind Engineering. In the present paper, LES are performed aiming at reproducing the modifications occurring in the flow when turbulent inflow conditions are adopted. In order to synthetically produce the unsteady inlet condition, a divergence-free and spatially correlated fluctuations field is generated by means of the Modified Discretizing and Synthesizing Random Flow Generator technique. The obtained synthetic fluctuations are imposed in the computational domain by modifying the velocity-pressure coupling algorithm in order to avoid nonphysical pressure fluctuations. Two configurations, corresponding to mild and strong incoming turbulence levels, are investigated highlighting the role played by the spanwise domain size. Results are compared to experimental data showing good agreement between experiments and numerical simulations.